Development of Managerial Skills for Cooperation Managers: Training and Mentoring - Fahamsyah, Mohammad Hatta; Rakhmat, Adriana Syariefur; Yaqin, Hamdan Ainul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program aimed at enhancing managerial competencies was conducted at Koperasi Simprug Garden through a combination of training and mentoring. The program focused on improving key areas such as leadership, financial planning, and member engagement strategies. A needs assessment identified gaps in these areas, and customized training modules were developed to address them. Over two months, 20 cooperation managers participated in interactive workshops and one-on-one mentoring sessions. The results demonstrated significant improvements in participants' knowledge and skills, with 85% of participants enhancing their understanding of financial reporting and 70% applying new leadership strategies in their roles. Additionally, member satisfaction increased by 15% within three months post-training.